Growth, nodulation and nutrient uptake as influenced by chickpea based intercropping systems under rainfed conditions - Alam, M.I. (Annals of Agricultural Research, 2017)
An experiment to study the "Spatial arrangement and fertility levels in chickpea (Cicer arietinum)based intercropping system under rainfed condition" was carried out during rabi-seasons of 2009-10 and 2010-11 at Tirhut College of Agriculture, Dholi Farm of Rajendra Agricultural University,Pusa, (Samastipur) , Bihar. Sole chickpea recorded higher number of branches/plant, dry matteraccumulation root length, root dry weight, number and dry weight of nodules/plant than 6:1 and6:2 row ratios of chickpea + mustard and chickpea + linseed. Among the row ratio in intercroppingsystems, chickpea + linseed (6:1) expressed better growth and dry matter accumulation than chickpea+ mustard in 6:1 and 6:2 ratio. The growth parameters of chickpea did not vary significantly due tofertility levels. Number of branches and dry matter accumulation of mustard and linseed werehigher in 6:1 row ratio of chickpea + mustard and chickpea + linseed than sole crops. As growthparameters of mustard and linseed were significantly higher at 100% RDF than 50% RDF exceptplant height of mustard and linseed. Nutrient uptake by chickpea did not vary significantly amongthe intercropping systems. However sole chickpea recorded significantly higher uptake ofphosphorus and potassium than chickpea + mustard and chickpea + linseed in both the row ratiowhile nitrogen uptake in sole chickpea significantly higher over 6:2 row ratio of chickpea + mustardand chickpea + linseed at both the row ratio of chickpea + mustard . Nutrients uptake by chickpeadid not vary significantly due to different levels of fertilizers. Total uptake of N, P and K by mustardand linseed in both the years were significantly higher in sole stand than their intercropping system.Among the row ratio in intercropping systems, 6:2 row ratio of both the intercropping systemsrecorded significantly higher uptake of these nutrients by mustard and linseed than 6:1 row ratio.The nutrients uptake recorded at 100% and 75% RDF were at par with each other and significantlyhigher over 50% RDF. Land equivalent ratio (LER) did not vary significantly among the row ratio inintercropping systems, only 6:1 row ratio of chickpea + mustard recorded significantly higher LER(1.2) over sole chickpea. LER did not vary significantly among different fertilizer levels. Chickpea+ mustard in 6:1 row ratio altogether recorded maximum chickpea equivalent yield (2367 kg ha–1)and net return (Rs. 44.8 Thousands ha–1) however, B:C ratio was higher under 6:2 row ratio ofchickpea + mustard (2.10) which was at par with 6:1 row ratio of chickpea + mustard (2.08). Chickpea+ mustard in both the row ratio recorded significantly higher chickpea equivalent yield, net returnand B:C ratio over chickpea + linseed in both the row ratio and sole chickpea. chickpea equivalentyield, gross return, net return, B:C ratio and LER did not varied significantly among the fertilizerlevels.